Manajemen Fundraising Potret Yayasan Badan Wakaf Universitas Islam Indonesia Yogyakarta dalam Menggalang Wakaf - Miftahul Huda (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2014)
The development of a waqf nadhir is currently important in an effort to strengthen and develop waqf continuously for the benefit of mauqu>f